Observation of "complete clinical response" in rectal cancer after neoadjuvant chemoradiation: The Flinders experience. (22nd June 2018) - Sposato, Luigi A.; Lam, Yick; Karapetis, Chris; Vatandoust, Sina; Roy, Amitesh; Hakendorf, Paul; Dwyer, Andrew; de Fontgalland, Dayan; Hollington, Paul; Wattchow, David
Abstract: Aim: Observation with close follow‐up ("watch and wait") is a recognized treatment option in patients who achieve a complete clinical response to long course chemoradiotherapy. This review of a prospective database aims to evaluate the clinical outcomes among patients with a complete clinical response managed with observation. Methods: A prospective study of 32 patients who achieved a complete clinical response was undertaken. The primary outcomes measured were overall and recurrence‐free survival, and rate of organ preservation in patients who deferred immediate surgery. Results: Seven patients developed local regrowth over a median follow‐up period of 38 months (range, 9–91 months). Median time to detection was 12 months. All seven underwent salvage surgery with complete surgical clearance. One patient developed combined local and systemic recurrence following a low anterior resection. Organ preservation was possible in 25 (78%) patients who sustained a complete clinical response with no evidence of local regrowth or disease recurrence. Among the patients who sustained a complete response, two developed isolated systemic disease. Overall and recurrence‐free survival was 95.7% and 87.0%, respectively. Conclusion: The majority of patients with rectal cancer who achieved a complete clinical response after chemoradiotherapy and managed with a "watch and wait" approach preserved their rectum and did not develop cancer relapse. Salvage surgery was achieved in all patients who developed local regrowth. The study supports a period of observation in rectal cancer patients who achieve a complete clinical response.